Extraction and application of quantitative indexes for mineralization-alteration in non-magmatic epigenetic hydrothermal deposits--a case of the super-large germanium-rich lead-zinc deposit in Huize, Southwest China - Yu, Jiuli; Zhang, Yan; Han, Runsheng; Wei, Pingtang; Li, Fenghao; Gu, Hanzhang; Wu, Jianbiao (Frontiers in Earth Science, 2026)
The Northeast Yunnan, which is an integral part of the Sichuan-Yunnan-Guizhou, contains approximately 20 million tons of metal reserves. This area provides an ideal location to evaluate relationship between alteration of the surrounding rocks and the ore body and most wall-rock are carbonates. Wall-rock alteration is a distinct feature of this type of deposit. It is the most direct and accurate indicator for prospecting blind ore bodies; however, it is limited by quantification and therefore cannot be applied. In this study, we examined the Huize super-large lead-zinc deposit in the Northeast Yunnan as an example and proposed quantitative indicators for alteration in the mining area. Based on quantitative alteration methods, including the alteration index (AI), carbonate-pyrite index (CPI), composite index (CI), and alteration box plots, five distinct alteration zones have been delineated within the Huize lead-zinc deposit. The above indices allowed us to determine the patterns of change in elements within the alteration zones and extract the characteristic indexes of these zones. The comprehensive analysis demonstrated that 1) the AI consists of AIMgO and AICaO, which are effective indicators for distinguishing between dolomitization and calcitization; 2) pyrite mineralization is closely related to various types of mineralization elements, and the CPI can be used to assess the strength of pyrite mineralization in different zones; and 3) the CI, comprising the AI and CPI, can effectively reflect the characteristics of alteration zones. The quantitative indexes of each alteration zone are as follows: distal end zone V (CI < 50), zone Ⅳ (51 < CI < 80), intermediate zone Ⅲ (81 < CI < 95), proximal zone Ⅱ (96 < CI < 98), and ore body Ⅰ (99 < CI) zones. In addition, this study utilized the CI to predict the hidden ore body in the deep middle section, which provides a theoretical basis for enriching the quantitative indexes of lead-zinc deposits in the Northeast Yunnan Ore Concentration and realizes the rapid delineation of the target area of similar deposits.